Sound intentions the workings of rhyme in nineteenth-century poetry - McDonald, Peter, 1962- (Oxford : Oxford University Press, 2013)
A pioneering stylistic study of major nineteenth-century poets with a special concentration on the ways in which rhyme becomes a mode of meaning.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: English poetry -- 19th century -- History and criticism; Rhyme